2013
DOI: 10.1179/2045772313y.0000000093
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive management of pressure ulcers in spinal cord injury: Current concepts and future trends

Abstract: Pressure ulcers in spinal cord injury represent a challenging problem for patients, their caregivers, and their physicians. They often lead to recurrent hospitalizations, multiple surgeries, and potentially devastating complications. They present a significant cost to the healthcare system, they require a multidisciplinary team approach to manage well, and outcomes directly depend on patients' education, prevention, and compliance with conservative and surgical protocols. With so many factors involved in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(114 citation statements)
references
References 66 publications
3
103
0
1
Order By: Relevance
“…20 The prolonged bed rest associated with MAP targeting accentuates SCI patients' already high risk of deep venous thrombosis and may be associated with an elevated risk of pressure sores, nosocomial infections, and deconditioning. [33][34][35][39][40][41] In patients who show these or other adverse effects early in their course of care, a decreased length of administration may be appropriate, given that the risks of blood pressure augmentation 20 likely increase over time while the benefits seem to decrease. Moreover, these data suggest that it may be appropriate to aggressively treat patients for the first 1-2 days even if their deficits are mild or if they are presumed to be high risk for complications.…”
Section: Literature To Datementioning
confidence: 99%
“…20 The prolonged bed rest associated with MAP targeting accentuates SCI patients' already high risk of deep venous thrombosis and may be associated with an elevated risk of pressure sores, nosocomial infections, and deconditioning. [33][34][35][39][40][41] In patients who show these or other adverse effects early in their course of care, a decreased length of administration may be appropriate, given that the risks of blood pressure augmentation 20 likely increase over time while the benefits seem to decrease. Moreover, these data suggest that it may be appropriate to aggressively treat patients for the first 1-2 days even if their deficits are mild or if they are presumed to be high risk for complications.…”
Section: Literature To Datementioning
confidence: 99%
“…A prospective study of spinal cord patients not only found that sacral and ischial pressure ulcers were very common (43% and 15%, respectively), as might be expected, but also noted that the second most common location was on the heel (19%). 12,13 Nursing home patients have a pressure ulcer prevalence of 11% and are most likely to develop pressure ulcers over the sacrum or heels. 14,15 Nursing home patients were also found to have contractures at a prevalence of 55%.…”
mentioning
confidence: 99%
“…The genesis and progression of post -SCI sequelae is still in experimental stage and therefore the current management is not targeted towards their cause but remains symptomatic. [10] It is apparent that there is a dire need for an ideal strategy focused towards the initial causative factors that trigger secondary injury processes to curtail all the sequalae of SCI. Recent reports suggest that extremely low frequency magnetic field (ELF-MF; 0.3 to 100 Hz) is beneficial in restoration of physiological functions in SCI also.…”
Section: Introductionmentioning
confidence: 99%